Level of satisfaction and preferences on design elements of houses among the disabled community in Kuala Lumpur and Selangor - Ab Rahman, Syakir Amir; Samsudin, Nasriah; Mohamed Osman, Mariana; Bachok, Syahriah; Rabe, Noor Suzilawati (2017)
Owning a residential property provides sense of security which leads to happiness, productive and fulfilling of one live. Moreover, home ownership able to create stability and improve the quality of life of the disabled communities. As Malaysia approaches developed status and becomes a high – income economy by 2020, the housing industry needs to be adaptive to demand for special groups. Everyone shares the right to a decent standard of living. Essential to the achievement of this standard and therefore to the fulfillment of human life beyond simple survival is access to adequate housing. According to Lusher, 1998, the universal home includes thoughtful and well – planned features that make the residence more usable by all family members. Universal homes incorporate universal design principles, resulting in a living environment that can, with little difficulty and expense, be adapted to virtually any user’s long term comfort, safety and ease. The aim of this paper is to study on the preferences and level of satisfaction on design factor in owning residential property among the disabled community in Kuala Lumpur and Selangor. This study looked at the main preferences in term of the housing’s design among the disabled community in owning residential property and the level of satisfaction towards the current design of their residential property. This study was carried out by using the quantitative approach where a questionnaire survey were distributed to 800 of respondents among the disabled community with mainly focused on two categories of disabilities, the physical and visual impairment. The outcome of this study will describe the preferences in owning residential property and level of satisafaction among the disabled community on the design of their residential property. It concludes by providing housing strategy in planning the design of residential property for the disabled community in Kuala Lumpur and Selangor.